Constructing Self Awareness Using Education Human Value In School Culture - Dewa Nyoman Wija Astawa (Penerbit STKIP PGRI Bangkalan, 2019)
The big number of poverty in Indonesia impact to the hope of having a free learning service, especially education for early age and elementary school students from the less fortunate families. Many people usually ask the quality of such kinds of free of charge schools. The low price makes a low standard for the students. Denpasar Sathya Sai School has proven that the free learning service does not mean the standard quality of the school is low. Using a qualitative approach, this case study was conducted at the Denpasar Sathya Sai School, which has distinctive characteristics. The data were extracted through in-depth observation of the learning activities and learning environment of children in school and FGD (focus group discussion) with classroom teachers, school of kindergarten head, principal of elementary school, foundation and parents. The analysis is done on the text obtained from observation and FGD